Rancang Bangun Sensor Cahaya Pendeteksi Api Pada Robot Cerdas Pemadam Api Politeknik Negeri Semarang - Supriyo, Bambang; Sayekti, Ilham (Teknik Elektro - Politeknik Negeri Semarang, 2017)
Light sensor for fire detection has a significant role in Inteligent Fire Fighting Robot, because the detection result of the sensor is used to detect the availabilty of the fire source (candle light) in a room. If the fire is detected, then the robot will move to the fire source and finally extinguish the fire. A photo transistor which is sensitive to infra red light is used as the sensor. The objective of the research is to test the photo transistor circuit and to observe the voltage response of the emitter pin of the photo transistor with respect to the fire for various distances from 10 cm to 100 cm. The collector pin of the photo transistor is connected to +5 Volt power supply, while the emitter part is connected to ground via the emitter resistor (Re). The emitter voltage of the phoro transistor is read via Analog Input Pin A0 of Arduino UNO. This voltage represents the strength level of the fire detected by the photo transistor. The data communication between Arduino UNO and computer is serially established via USB port. The data logging process is performed using Matlab/Simulink. Arduino UNO microcontroller is used to process the data such that the correlation between the sensor voltage and the sensor distance from the fire source can be identified. Theexperimental results show that the use of emitter resistor (Re) 10 kOhm has the best voltage response with respect to the fire source for the distance of 10 cm to 60 cm, compared to Re = 4k7 Ohm (for distance from 15 cm hingga 30 cm) and Re = 22k Ohm (for distance of 10 cm hingga 35 cm). As a result, the combination of photo transistor and resistor (Re) of 10 kOhm can be applied for fire detection circuit for the distance up to 60 cm.Keywords : arduino uno, photo sensor, fire sensor